Tourist spending on food and the local cuisine of the Patate canton - Lesano Martínez, Vanessa (2023)
Ecuador is a country with the 4 worlds, full of legacies and intangible cultural heritage such as gastronomy, it is one of the main economic engines of tourist destinations. Tourists are enriched and learn from the traditional knowledge of the inhabitants through experience and history in the place. The objective of this research is to identify tourist spending on food and spread the local cuisine of the Patate canton. The methodology used is a mixed approach, therefore, three instruments were applied, the interview, the food atlas cards and the survey. For the qualitative part, experts of the different characteristics of the local cuisine were carried out in the field. On the other hand, a survey of tourists was carried out in order to know the tourist food expenditure in the canton and their motivation for visiting. There is a high percentage of tourist spending on food and the local cuisine of Patate is represented by products that are connected to the history of the canton. As a result, a proposal suitable for people with visual disabilities was obtained, it is a spoken magazine that fulfills the function of adapting to all visitors and thus achieving accessible tourism. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/1961